2001
DOI: 10.1080/00437956.2001.11432508
|View full text |Cite
|
Sign up to set email alerts
|

Pitch range and women's sexual orientation

Abstract: RACHELLEWAKSLER'------------------------ Pitch range and women's sexual orientationAbstract. The interaction between intonational patterns and speaker gender has long been noted in the language and gender literature (e.g., Brend 1972, Lakoff 1975, McConnell-Ginet 1983, Ohara 1992. It has also been hypothesized (Moonwomon 1985, Queen 1997) that intonation may be a locus of difference between lesbian and heterosexual women's speech. This paper investigates the question of whether there is an interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…For example, several studies of heterosexual and homosexual speakers have reported few differences in voice pitch (Gaudio, 1994;Lerman & Damste, 1969;Linville, 1998;Waksler, 2001). Because voice pitch is ultimately traceable to the size of the larynx, this outcome suggests that there are no basic differences in the size of the laryngeal apparatus between heterosexual and homosexual speakers.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…For example, several studies of heterosexual and homosexual speakers have reported few differences in voice pitch (Gaudio, 1994;Lerman & Damste, 1969;Linville, 1998;Waksler, 2001). Because voice pitch is ultimately traceable to the size of the larynx, this outcome suggests that there are no basic differences in the size of the laryngeal apparatus between heterosexual and homosexual speakers.…”
Section: Introductionmentioning
confidence: 84%
“…Some homosexual men spoke with relatively high voice pitch but so too did some heterosexual men. Subsequent studies have similarly failed to find robust differences in mean voice pitch between homosexual men and women and their heterosexual counterparts, although some have reported differences in longer-term pitch modulation patterns and other elements of prosody (Gaudio, 1994;Munson, McDonald, DeBoe, & White, 2006;Rogers, Jacobs, & Smyth, 2001;Smyth, Jacobs, & Rogers, 2003;Waksler, 2001). Hence, although some homosexual men and women may speak with a relatively high or low voice pitch, respectively, or with more exaggerated or attenuated pitch modulation in ways reminiscent of the opposite-sex, these most basic dimensions of the stereotypes of homosexual men and women appear not to be entirely reliable.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, differences in the fundamental frequency (i.e. pitch), which have been widely theorized as indexical of sexual orientation (with gay men assumed to have greater pitch range than straight men and lesbians assumed to have narrower pitch ranges than straight women), have been inconclusive and few significant differences in pitch range have been found (Gaudio 1994; Moonwomon 1997; Waksler 2001; Smyth et al. 2003; Levon 2006).…”
Section: Experimental Approaches To Language and Sexualitymentioning
confidence: 99%
“…In particular, differences in the fundamental frequency (i.e. pitch), which have been widely theorized as indexical of sexual orientation (with gay men assumed to have greater pitch range than straight men and lesbians assumed to have narrower pitch ranges than straight women), have been inconclusive and few significant differences in pitch range have been found (Gaudio 1994;Moonwomon 1997;Waksler 2001;Smyth et al 2003;Levon 2006). 11 Pierrehumbert et al (2004) found, however, that there were specific differences in the vowel spaces of speakers who identified themselves with different sexual orientations and concluded that those differences provided evidence that gay men and lesbians' manipulations of the vocal tract are learned behavior rather than somehow biological in nature.…”
Section: Experimental Approaches To Language and Sexualitymentioning
confidence: 99%